Effect of Guava Fruit Aqueous Extract on Haematological Profile of Carbon Tetrachloride Induced Rat - Rahmawati, Aulia Nur; Lestari, Mastuti Widi; Saputri, Alip Desi Suyono; Berliana, Adinda Aisyah; Fattany, Davan Nur; Cahyaningrum, Oktavia Fajar (Jurnal Biologi Tropis, 2024)
Psidium guajava or guava have many potential value, including as antioxidant. Psidium guajava fruits have been reported that contain essential oil, flavonoid, polyphenol, ascorbic acid, dan tocopherol. This study aims to investigate weight gain and heamatological alteration as an effect from administration of red guava fruit extract in male wistar rats after carbon tetrachloride. This study was experimental design using male wistar rats as an experimental animals. The results of the study were red guava fruit aqueous extract can control weight gain in model animal, increasing of LYM, MCMC dan WBC. It indicated that Psidium guajava fruit is potentially be able to be used as an pharmaceutical product because of its antioxidant ability.